1996
DOI: 10.1523/jneurosci.16-16-05141.1996
|View full text |Cite
|
Sign up to set email alerts
|

Actions of Substance P on Rat Neostriatal NeuronsIn Vitro

Abstract: Actions of substance P (SP) on the neostriatal neurons in in vitro rat slice preparations were studied via whole-cell patch-clamp recording. Almost all large aspiny neurons (cholinergic cells) and half of the low-threshold spike (LTS) cells (somatostatin/ NOS-positive cells) showed depolarization or an inward shift of the holding currents in response to bath-applied SP in a dosedependent manner. In contrast, no responses were observed in fast-spiking (FS) cells (parvalbumin-positive cells) and medium spiny cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 50 publications
3
73
0
Order By: Relevance
“…Despite the fact that we cannot rule out that SP might induce a slow depolarization by interacting with other neurotransmitter systems or ionic pumps different from Na ϩ /K ϩ ATPase, all our experiments are consistent with the modulation of a low-voltageactivated, TTX-insensitive sodium current (Delmas et al, 1997): (1) this current is activated by various neurotransmitters including SP (Koyano et al, 1993;Aosaki and Kawaguchi, 1996); (2) the current is activated at resting potential (Delmas et al, 1996;Gola et al, 1998a,b); (3) because the slow depolarization persisted in the presence of SP, it does not undergo inactivation; (4) this current is TTX insensitive, yet sodium dependent (Wang and Aghajanian, 1987;Raggenbass and Dreifuss, 1992;Delmas et al, 1996); (5) this current is not blocked by TEA (10 -20 mM) (Alberi et al, 1993;Delmas et al, 1996); (6) characterizations of this current have also described the absence of an obvious change in input resistance (for review, see Delmas et al, 1997); and (7) lowering the physiological levels of calcium (2-25 mM) to 0.1 mM reversibly enhances the low-threshold sodium currents (Raggenbass and Dreifuss, 1992;Alberi et al, 1993;Delmas et al, 1996), which explains the observed dramatic depolarization of respiratory neurons caused by SP in low calcium (Fig. 6 A).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Despite the fact that we cannot rule out that SP might induce a slow depolarization by interacting with other neurotransmitter systems or ionic pumps different from Na ϩ /K ϩ ATPase, all our experiments are consistent with the modulation of a low-voltageactivated, TTX-insensitive sodium current (Delmas et al, 1997): (1) this current is activated by various neurotransmitters including SP (Koyano et al, 1993;Aosaki and Kawaguchi, 1996); (2) the current is activated at resting potential (Delmas et al, 1996;Gola et al, 1998a,b); (3) because the slow depolarization persisted in the presence of SP, it does not undergo inactivation; (4) this current is TTX insensitive, yet sodium dependent (Wang and Aghajanian, 1987;Raggenbass and Dreifuss, 1992;Delmas et al, 1996); (5) this current is not blocked by TEA (10 -20 mM) (Alberi et al, 1993;Delmas et al, 1996); (6) characterizations of this current have also described the absence of an obvious change in input resistance (for review, see Delmas et al, 1997); and (7) lowering the physiological levels of calcium (2-25 mM) to 0.1 mM reversibly enhances the low-threshold sodium currents (Raggenbass and Dreifuss, 1992;Alberi et al, 1993;Delmas et al, 1996), which explains the observed dramatic depolarization of respiratory neurons caused by SP in low calcium (Fig. 6 A).…”
Section: Discussionsupporting
confidence: 52%
“…SP activates voltage-dependent Ca 2ϩ channels, voltage-dependent K ϩ conductances, Cl Ϫ currents, Ih currents, voltage-dependent Na ϩ channels, and nonselective cationic channels (Adams et al, 1983;Stanfield et al, 1985;Bley and Tsien, 1990;Shen and North, 1992;Bertrand and Galligan, 1994;Aosaki and Kawaguchi, 1996). In most neurons, SP depolarizes membrane potential by decreasing resting K ϩ conductances (Akasu et al, 1996;Lepre et al, 1996;Ptak et al, 2000;Yasuda et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…We measured, therefore, the effects of 100 M hydroxylamine after 10 min preincubation of the slices in a solution containing 1 M -conotoxin GVIA, 20 M nifedipine, and 20 nM -agatoxin TK (to block, respectively, N-type, L-type, and P-type high voltage-activated calcium channels) and 300 M MCPG plus 10 M [D--Arg 1 ,D--Pro 2 ,D--Trp 7,9 ,Leu 11 ]-SP (to block mGluRs and substance P receptors, respectively). Noticeably, -conotoxin GVIA has already been found to block synaptic inputs to striatal cholinergic interneurons (Pisani et al, 2000), and MCPG and [D--Arg 1 ,D--Pro 2 ,D--Trp 7,9 ,Leu 11 ]-SP prevented in previous studies the depolarizing effects mediated by mGluR and substance P receptor activation on these cells (Aosaki and Kawaguchi, 1996;Takeshita et al, 1996). This pharmacological treatment, however, failed to affect the amplitude of the NOinduced membrane depolarization of striatal interneurons ( p Ͼ 0.05; n ϭ 5; Fig.…”
Section: No-mediated Membrane Depolarization Of Striatal Cholinergic mentioning
confidence: 82%
“…Like in other areas of the brain, SP is released in the BG due to an elevation in Ca 2+ (Otsuka www.intechopen.com and Yoshioka, 1993). Once released, it may bind to NK 1 receptors located on striatal interneurons to increase the firing rate and depolarise membrane potentials causing the release of other BG neurotransmitters such as GABA, glutamate and acetylcholine (Aosaki and Kawaguchi, 1996, Bailey, et al, 2004, Kemel, et al, 2002. It is now known that NK 1 receptors are also located on 90% of DA neurons in the SNc (L-W. Chen, et al, 2004).…”
Section: Substance P Regulation Of Basal Ganglia Functionmentioning
confidence: 99%